2007
DOI: 10.1186/bcr1668
|View full text |Cite
|
Sign up to set email alerts
|

Identification of women with an increased risk of developing radiation-induced breast cancer: a case only study

Abstract: Introduction Radiation exposure at a young age is one of the strongest risk factors for breast cancer. Germline mutations in genes involved in the DNA-damage repair pathway (DDRP) may render women more susceptible to radiation-induced breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 38 publications
0
52
0
1
Order By: Relevance
“…5,[13][14][15][16][17][18][19] For homozygous carriers, our observations indicate that (contralateral) breast cancer risk may be as high as to justify preventive mastectomy (or at least intensified screening), but longitudinal studies on more cases are needed to arrive at more accurate risk estimates.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…5,[13][14][15][16][17][18][19] For homozygous carriers, our observations indicate that (contralateral) breast cancer risk may be as high as to justify preventive mastectomy (or at least intensified screening), but longitudinal studies on more cases are needed to arrive at more accurate risk estimates.…”
Section: Discussionmentioning
confidence: 93%
“…3,[10][11][12][13] Breast cancer patients heterozygous for 1100delC also have an increased risk of developing contralateral breast cancer when compared with wild-type breast cancer patients. 5,[13][14][15][16][17][18][19][20] The contralateral breast cancer risk may be even higher when radiotherapy has been given to treat the first tumor. 15,19 It must be noted that in women who also carry a pathogenic BRCA1/2 mutation the 1100delC allele does not seem to modify breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…The germline mutation 1100delC truncates the CHEK2 protein, thereby abolishing the kinase function (Wu et al, 2001). Epidemiological evidence to substantiate increased radiosensitivity among carriers is, however, sparse (Bernstein et al, 2006;Broeks et al, 2007). Also, although a study conducted in Belgium suggested that breast cancer patients with a CHEK2*1100-delC mutation are, in general, not characterised by a distinct enhanced chromosomal radiosensitivity, this conclusion was based on only four breast cancer cases with the mutation who were compared with healthy controls without the mutation (Baeyens et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides additional insights into the findings of the few published studies that have examined risk of CBC associated with RT among BRCA1/BRCA2 carriers (12,(26)(27)(28)(29)(30). The multi-center follow-up study of breast cancer patients attending high risk clinics conducted by Pierce and colleagues (28, 31) compared patients treated with breastconserving surgery and RT.…”
Section: Discussionmentioning
confidence: 95%
“…Their finding of an increased risk of CBC among carriers is also consistent with ours. In a case-only study, Broeks et al examined 247 CBC cases to identify carriers of a germline mutation in ATM, BRCA1/BRCA2, or CHEK2 (26) and found an interaction of RT with carriers of these mutations. However, this study only examined risk by aggregating genes and the extent of interaction attributable to BRCA1/BRCA2 carrier status was not reported.…”
Section: Discussionmentioning
confidence: 99%